Village Expansion in Indramayu Regency: Case Study of Village Expansion in Kalimati Village, Jatibarang District, Indramayu Regency - Ismanudin; Ibrohim (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2024)
The study of policy implementation regarding village expansion is an important aspect to know. This research is to determine the process of village expansion in Kalimati Village, Jatibarang District, Indramayu Regency. The process of expanding Kalimati Village, Jatibarang District in this research is the process of expanding one village into two villages. The main village that was expanded was Kalimati Village, Jatibarang District, while the planned village results that were expanded were Prupugan Village, Jatibarang District, which was previously called the Prupugan Block, Kalimati Village, Jatibarang District. The process of expanding Kalimati Village, Jatibarang District, which is viewed from the aspects of planning, organization, movement/implementation and supervision in general, has been implemented in accordance with the provisions of applicable laws and regulations. The village expansion process has been running since the end of 2006, however, due to the results of the village expansion, until now the Indramayu Regency Government has not given clear status, namely whether the village has been expanded or not expanded.